2020
DOI: 10.21276/obgyn.2020.6.2.11
|View full text |Cite
|
Sign up to set email alerts
|

GeneXpert positivity and evaluation of rifampicin resistance among endometrial biopsy specimens for the diagnosis of Genital Tuberculosis

Abstract: Objective: The aim of this study was to find out the GeneXpert positivity among endometrial biopsy specimens for diagnosis of genital tuberculosis. Materials and Methods: A retrospective study was conducted from January 2019 to June 2019 on all women clinically and radiologically diagnosed with infertility, dyspareunia, menstrual irregularities and pelvic inflammatory disease. Endometrial biopsies were taken from all cases and subjected to GeneXpert test for detection of Mycobacterium tuberculosis. Result: Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…In addition, we obtained results of RIF resistance by Xpert, wherein three of six cases positive for Mtb identification were also positive for RIF resistance. Xpert results of this study are well in consensus with the previous reports on urine/EB specimens of male/female UGTB cases, wherein sensitivities were in the range of 8-41Á3% but a high specificity (100%) was attained, against CRS/culture (Chen et al 2019; Kashyap et al 2020;Tiwari et al 2020). The present findings and the previous reports suggest that Xpert can be employed as an excellent rule-in test for UGTB diagnosis but not as a good rule-out test.…”
Section: Comparison Of Genexpert Vs M-nested Pcrsupporting
confidence: 91%
“…In addition, we obtained results of RIF resistance by Xpert, wherein three of six cases positive for Mtb identification were also positive for RIF resistance. Xpert results of this study are well in consensus with the previous reports on urine/EB specimens of male/female UGTB cases, wherein sensitivities were in the range of 8-41Á3% but a high specificity (100%) was attained, against CRS/culture (Chen et al 2019; Kashyap et al 2020;Tiwari et al 2020). The present findings and the previous reports suggest that Xpert can be employed as an excellent rule-in test for UGTB diagnosis but not as a good rule-out test.…”
Section: Comparison Of Genexpert Vs M-nested Pcrsupporting
confidence: 91%
“…In addition, the low positivity samples showed higher Rif indeterminate results thus further obscuring use of Xpert MTB/RIF ULTRA in these samples. This is similar to lowpositivity percentage obtained by Kashyap et al in GUN; and high-positivity percentage obtained by Agarwala et al in-liver abscess; and low-positivity percentage, in pleural fluid, and high-positivity percentage in lymph nodes and abscess by Chaudhary et al [6][7][8] False positive and false negative calls by Xpert MTB/ RIF have been reported by authors earlier. This study showed that percentage drug resistance for Rif, streptomycin was similar to resistance % published by Lohiya et al which had included a total of 90 nonduplicate studies published till 2018 for their review.…”
Section: Mgit Based Drug Susceptibility Testingsupporting
confidence: 88%